Navigation Of Mobile Robot Using Global Positioning System (GPS) And Obstacle Avoidance System With Commanded Loop Daisy Chaining Application Method - Mohamad Hanif, Abd Hamid; Abdul Hamid, Adom; Norasmadi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org